Réinventer la nature en ville (éditions Quae, 2026)
Faced with climate change, the growing desire of urban residents to access nature, and the introduction of new regulations, urban nature represents one of the main components of sustainable urban development. This book explores how local authorities are reinventing urban nature by integrating environmental and social dimensions. It traces the history of urban nature and the public policies that support it, and offers a cross-disciplinary analysis by scientists and practitioners of new challenges: water management, biodiversity, soil, health, and climate change adaptation. It also shows the consequences of evolving public policies and knowledge on new urban landscapes, whether heritage, recreational, or food-producing. Finally, it explores the hybrid governance of nature projects within local authorities, involving institutional actors, associations, citizen, to address planning, design, and management of urban nature at all scales. The book advocates for strengthening dialogue between elected officials, scientists, and practitioners in order to meet the increasing need for scientific, technical, and strategic training, as well as for the governance of partner collectives, with urban nature becoming a major object of democratic engagement. It is intended for elected officials, local public service managers, consulting firms, agencies, and associations involved in urban development.